TEKNIK PENGEMBANGAN KAWASAN RUMAH PANGAN LESTARI DI DAERAH ISTIMEWA YOGYAKARTA (TECHNICAL DEVELOPMENT OF SUSTAINABLE FOOD HOUSEHOLD AREA IN DAERAH ISTIMEWA YOGYAKARTA) - Werdhany, Wiendarti Indri; Gunawan, Gunawan (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2012)
Sustainable Food Household Area (KRPL) is one of the programs the Ministry of Agriculture in order to optimize the lawn yard in an region. The aim of KRPL program is developing the ability of families and communities in self sufficient the food and nutritions in a sustainable manner. The rapid development of KRPL depends on appropriate development techniques. Development techniques of KRPL in Yogyakarta through the stages (1) the formation of the group, (2) identification of group needs, (3) the preparation of action plans, (4) training, (5) creation nurseries and (6) design of KRPL area. Appropriate stages of the development techniques to realize replication KRPL quickly and is able to provide real benefits for the family. KRPL in Daerah Istimewa Yogyakarta has grown rapidly. In 2011, KRPL by one farmer group in Gunungkidul district, in 2012 has been developed in 4 districts and 1 city. In 2012, the number of KRPL groups in Yogyakarta as many as 12 groups, consisting of 8 women farmer groups and 4 farmer groups. Each KRPL in Daerah Istimewa Yogyakarta have characteristic such as having a nursery, carried out by number of RPL who joined the group and stay in the region. The benefits for families is to get the cost savings for food consumption which range between Rp. 50.000,00 to Rp.300.000,00 per month per family. The value of savings is limited, due to the number of plants cultivated still limited by each family.